Burning the straits: indignation and hospitality in Ben Jelloun. Issue 4 (8th August 2018) - Schoene, Adam
ABSTRACT: Tahar Ben Jelloun's Partir (2006) shines a spotlight upon a society plagued by poverty and corruption, where 'burning' refers both to the act of migrants setting sail across the sea, and to that of torching their identity documents to avoid repatriation. The intertwined fates of protagonists Azel and Miguel in their respective homelands of Morocco and Spain capture the dual nature of refuge and endangerment in the concept of hospitality, embodied within their national affiliations and in their fraught same-sex relationship. I follow the course of these voyagers into the unknown, arguing that Ben Jelloun upsets both political and sexual borders to reveal an omnipresent yearning for a better future, born from the flames of indignation. I situate Partir within the context of ongoing struggles around migration, reading it as a quest to achieve the cosmopolitan ideals of ethics and hospitality, but of a hospitality that is less focused on guest versus host and is aligned closer with conviviality.